The coexistence of superior intrinsic piezoelectricity and thermoelectricity in two-dimensional Janus α-TeSSe. Issue 47 (29th November 2021) - Chen, Shaobo; Chen, Xiangrong; Zeng, Zhaoyi; Geng, Huayun; Yin, Huabing
Abstract : A new group-VI Janus ternary compounds  α -TeSSe monolayer exhibits outstanding piezoelectric and thermoelectric performances, which has broad application prospects in the fields of piezoelectrics and thermoelectrics. Abstract : Piezoelectric and thermoelectric materials that can directly convert mechanical and thermal energies into electricity have attracted great interest because of their practical applications in overcoming the challenges of the energy crisis. In this research, a new family of two-dimensional (2D) group-VI Janus ternary compounds with α and γ phases are predicted. After the stability testing, only the α-TeSSe monolayer has dynamic and thermal stability. The band structure and the optic, piezoelectric, and thermoelectric performances of the Janus α-TeSSe monolayer are calculated via first-principles calculations. Janus α-TeSSe is a narrow indirect bandgap semiconductor with a value of 0.953 eV at the HSE06 functional considering the spin–orbit coupling (SOC), which is beneficial to its thermoelectric performance, and its excellent absorption coefficients indicate that it may be a promising optoelectronic material. The piezoelectric calculations show that Janus α-TeSSe exhibits not only appreciable in-plane piezoelectricity ( d 11 = 17.17 pm V −1 ) but also superior vertical piezoelectricity ( d 31 = 0.22 pm V −1 ). Furthermore, a new TransOpt code is used to calculate the electrical transport coefficients with a constant electron–phonon coupling approximation, which is more accurate than the constant relaxation time approximation. The origin of ultralow lattice thermal conductivity is also discussed in detail. Finally, ultrahigh ZT values of 0.77 and 1.95 occur in n-type and p-type doping at 600 K, respectively, indicating that it is a promising thermoelectric material. Our work demonstrates that Janus α-TeSSe monolayers have potential applications in optoelectronic, piezoelectric, and thermoelectric devices, which will greatly stimulate research-related experiments.